The genome sequence of the black scavenger fly, Nemopoda nitidula (Fallén, 1820) [version 1; peer review: 2 approved] - Steven Falk; Liam M. Crowley; Ruth Y. Akinmusola (Wellcome Open Research)
We present a genome assembly from an individual specimen of Nemopoda nitidula (Arthropoda; Insecta; Diptera; Sepsidae). The genome sequence has a total length of 178.40 megabases. Most of the assembly (99.2%) is scaffolded into 6 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 15.98 kilobases in length.